Interactions of heavy metal elements across sediment-water interface in Lake Jiaogang. (1st October 2021) - Kong, Ming; Zhu, Yanzhong; Han, Tianlun; Zhang, Shuai; Li, Jiuling; Xu, Xueting; Chao, Jianying; Zhang, Yimin; Gao, Yuexiang
Abstract: Heavy metal pollution in lake systems has arisen plenty of threats for public health because of its high toxicity, persistence, and bioaccumulation. Whereas heavy metals are inextricably linked with bioavailability in pore water and overlying water. Lake Jiaogang is classified as an important water-carrying lake situated in the northern part of the Anhui Province China. In recent years, water quality in this lake declined due to increasing fishery aquaculture, livestock, and tourism. This study aims to bring insight into the interactions of heavy metal elements across sediment-water interface in Lake Jiaogang. Four representative regions were selected, more than ten heavy metals were chosen to quantify by the Community Bureau of Reference, diffusive gradient in thin-film (DGT), and high-resolution pore water equilibrators. The results showed that most heavy metals corresponded with the reducible fraction, acid-soluble fraction, and oxidizable fraction in the Eastern area (sample 3 # ) and aquaculture area (sample 4 # ) were higher than that of emergent plant area (sample 1 # ), and floating plant area (sample 2 # ). The average fluxes of heavy metals (except Ni and Zn in sample 3 #, F value > 0 pg/cm 2 /d) in the four sampling sites were observed in the lower reaches ( F value < 0 pg/cm 2 /d). The vertical distribution of heavy metals was extracted by DGT, such as As (exclude 2 # ), Co, Fe, Mn, and Zn (contain 4 # ) showed an increased content with increasing depth in the four sampling sites. In the pore and overlying water, concentrations of heavy metals from the sample 3 # and 4 # were higher than those of sample 1 # and 2 # . Heavy metal pollution in anthropogenic activity areas was higher than those in areas with ecological vegetation, and risk control in this area should be strengthened. Graphical abstract: Image 1 Highlights: Interactions of heavy metal elements across sediment-water interface was observed. Vertical distribution of heavy metals was quantified by DGT and HR-Peeper. Significant positive correlation was revealed between the concentration of Mn and As. Relationships of the heavy metals were revealed between sampling sites and depth.